2013
DOI: 10.1080/14703297.2012.746512
|View full text |Cite
|
Sign up to set email alerts
|

Research self-efficacy of lecturers in non-university higher education

Abstract: Research self-efficacy of lecturers in non-university higher educationGriffioen, D.M.E.; de Jong, U.; Jak, S. AbstractDuring the last decade, the relationship between university and non-university higher education institutions has changed. As a contribution to the knowledge economy, non-university higher education institutions are expected to educate their students in research activities. Previously, teaching was the main responsibility of lecturers in non-university higher education, while research hardly pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…This scan was developed using the results of the study of Griffioen, de Jong and Jak (2013). They rated their own capabilities for conducting the generally accepted phases within a research: collecting suitable literature, choosing the right research design in accordance with the research questions, collecting the proper data in an efficient way using the right analysis and interpretation, being able to report on the research according to scientific standards and being able to transform the results into applications.…”
Section: The Surveymentioning
confidence: 99%
“…This scan was developed using the results of the study of Griffioen, de Jong and Jak (2013). They rated their own capabilities for conducting the generally accepted phases within a research: collecting suitable literature, choosing the right research design in accordance with the research questions, collecting the proper data in an efficient way using the right analysis and interpretation, being able to report on the research according to scientific standards and being able to transform the results into applications.…”
Section: The Surveymentioning
confidence: 99%
“…It is suggested that there should be further development in the specialized branch of knowledge of higher education for having a systematic approach in order to deal with the problems and issues aroused in the policy of higher education [59]. Thus, universities are expected to develop their students in research activities [24]. Difficulties faced by the higher education students in North Cyprus are related to not having enough support to carry out researches, academicians' not having satisfaction towards students, education and/or higher education in general, part-timers' not having sense of belonging to the university they teach totally, full-timer' and part-timers' not having office hours for the students to plan teaching and learning process, carry out researches and/or pose any questions university students would likely to ask them and finally most of the academicians' not having necessary PhD and/or EdD degrees to be able to teach at the university.…”
Section: Category 2: After Academic Mobility Factorsmentioning
confidence: 99%
“…Preferences concerning research aims are studied in both groups. In the Dutch hogescholen, lecturers are at the root of changing non-university higher education into more research-based organisations, since lecturers are the primary connection between the institution and the students (and often the main connection with the professional field) (Griffioen et al, 2013;van den Berg et al, 2000;Runhaar, 2008). Hence, their perceptions and activities will influence the direction and speed with which the proposed goals are reached or resisted (McRoy and Gibbs, 2009).…”
Section: Managers Lecturers and Educational Changesmentioning
confidence: 99%